Improving Effectiveness and Satisfaction of an Electronic Charting System in Taiwan. Issue 6 (November 2016) - Hsieh, Hsiao-Yen; Henker, Richard; Ren, Dianxu; Chien, Wan-Yi; Chang, Jia-Ping; Chen, Lifan; Tuite, Patricia K.
Abstract : Purpose/Objectives: An efficient but comprehensive documentation system is essential for reducing nursing workload and ensuring adequate time for direct patient care. A "focus" is a nursing diagnosis or patient problem. The purpose of this project is to review and revise the focuses in the electronic charting system and to develop new focuses for documentation of clinical pathways. In addition, this project evaluated the impact of these changes on time required for documentation and nurse satisfaction. Background/Rationale: In 2012, a large hospital in Taiwan implemented a self-developed electronic charting system that had 217 focuses in the database. Staff reported low job satisfaction and too much time on documentation. Three major issues were identified, including repetitious and redundant documentation, incorrect templates, and an incomprehensive database. Description: A clinical nurse specialist devised quality improvement project was implemented on one 50-bed surgical unit. Forty-one focuses were revised and 13 new focuses were developed for clinical pathways. The implementation of new focus templates enhanced evidence-based practice and prevented redundant documentation. Focus templates also incorporated nursing policies and/or patient education materials. Two outcome indicators, time spent documenting and nurse satisfaction, were evaluated 3 months after implementation. Outcomes: Documentation time decreased by 60% (from 138.5 to 55.8 hours) per week. The median documentation time per patient per day decreased from 18.4 minutes to 9.3 minutes. Average scores for satisfaction in usability, content, functionality, and effectiveness were increased. Conclusion: Evidence-based focus templates used for documentation can reduce documentation time and increase nurse satisfaction. Clinical nurse specialists play an important role in leading the development of quality improvement projects while improving work efficiency.